China : Global Crisis Avoided, Robust Economic Growth Sustained - Vincelette, Gallina Andronova; Manoel, Alvaro; Hansson, Ardo; Kuijs, Louis (2012)
This paper explores how the ongoing crisis, the policy responses to it, and the post-crisis global economy will impact China's medium-term prospects for growth, poverty reduction, and development. The paper reviews China's pre-crisis growth experience, including its relationship to global economic developments. It discusses the pace, composition, sources, and financing of growth during 1995-2007, and the impact of key external and domestic influences. The paper also analyzes the immediate impact of the global crisis on China's economic performance in 2009 and its likely impact in the short run. It then discusses the government's policy response, with a particular focus on the fiscal and monetary stimulus measures. Finally, the paper explores China's medium-term growth prospects in light of the crisis and the key policies for moving to a robust and sustainable growth path post-crisis.